Penguatan Tata Kelola Administrasi Pemerintahan Desa Berbasis Smart Village di Desa Karanggintung Kecamatan Sumbang Kabupaten Banyumas - Denok Kurniasih; Paulus Israwan Setyoko (Department of Public Administration, University Wijaykusuma Purwokerto, 2026)
The transformation of village governance has become a strategic issue in line with the increasing demand for public services, the dynamics of regional development, and the development of information technology. Karanggintung Village, Sumbang District, Banyumas Regency, is experiencing growth in residential areas and the development of community-based culinary tourism, which has resulted in increasing complexity in village administrative services. However, the capacity of village officials in managing government administration and utilizing information technology still faces various limitations. This community service activity aims to improve the understanding and capabilities of Karanggintung Village officials in managing government administration and public services through a smart village approach. The method used is a participatory and educational approach, which includes needs analysis, socialization of the smart village concept, training and mentoring, and monitoring and evaluation. The results of the activity indicate an increase in village officials' understanding of the principles of good governance, increased awareness of the importance of digitizing village administration, improved public service orientation, and strengthened village officials' capacity in managing more orderly and standardized government administration. However, challenges remain in implementing smart villages, particularly related to the readiness of village officials' human resources. This activity is expected to be the first step in encouraging the transformation of Karanggintung Village governance towards a more effective, transparent, and sustainable administrative system.